2017
DOI: 10.1158/0008-5472.can-16-1986
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 Promotes Pancreatic Ductal Adenocarcinoma by Regulating Inflammation in the Tumor Microenvironment

Abstract: Lipocalin-2 (LCN2) promotes malignant development in many cancer types. LCN2 is upregulated in patients with pancreatic ductal adenocarcinoma (PDAC) and in obese individuals, but whether it contributes to PDAC development is unclear. In this study, we investigated the effects of Lcn2 depletion on diet-induced obesity, inflammation and PDAC development. Mice with acinar cell-specific expression of KrasG12D were crossed with Lcn2-depleted animals and fed isocaloric diets with varying amounts of fat content. Panc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 61 publications
3
102
0
Order By: Relevance
“…However, the concrete mechanism is still unknown, further analysis was performed and two related hub genes (SUPV3L1 and SLC22A17) in three immune cells types of TCGA and GEO groups were regarded as hub genes for further validation, indicating that the two hub genes had a high connection with infiltration as well as prognosis. It has been reported that overexpression of SLC22A17 associated with poor prognosis of cancer, such as endometrial carcinoma, gliomas and hepatocellular [28][29][30], and Lipocalin-2 (LCN2) has the potential to alter immune cell infiltration and the tumor microenvironment in pancreatic ductal adenocarcinoma by downregulation of LCN2-specific receptor SLC22A17 [31]. These all indicate that SLC22A17 may influence prognosis through influencing immune cell infiltration and provided further evidence that SLC22A17 may play the same role in gastric cancer.…”
Section: Discussionmentioning
confidence: 75%
“…However, the concrete mechanism is still unknown, further analysis was performed and two related hub genes (SUPV3L1 and SLC22A17) in three immune cells types of TCGA and GEO groups were regarded as hub genes for further validation, indicating that the two hub genes had a high connection with infiltration as well as prognosis. It has been reported that overexpression of SLC22A17 associated with poor prognosis of cancer, such as endometrial carcinoma, gliomas and hepatocellular [28][29][30], and Lipocalin-2 (LCN2) has the potential to alter immune cell infiltration and the tumor microenvironment in pancreatic ductal adenocarcinoma by downregulation of LCN2-specific receptor SLC22A17 [31]. These all indicate that SLC22A17 may influence prognosis through influencing immune cell infiltration and provided further evidence that SLC22A17 may play the same role in gastric cancer.…”
Section: Discussionmentioning
confidence: 75%
“…Rather perplexing though, modulating LCN2 expression in human pancreatic cancer cells did not affect cell viability in vitro, but once engrafted LCN2-overexpressing tumors were smaller, poorly vascularized and had fewer metastases in an orthotopic nude mouse model (96). In contrast, in mice with diet-induced pancreatic cancer on a LCN2 −/− background had fewer and smaller tumors, less inflammation (reduced infiltration of CD45 + leukocyte cells and F4/80+ macrophages) and fibrosis compared to wild-type (95). Moreover, when murine tumor cells expressing LCN2 were implanted in LCN2 null mice, tumor growth was delayed and survival increased suggesting that expression in stromal…”
Section: Iron Transportmentioning
confidence: 91%
“…Lipocalin 2 (LCN2), also known as neutrophil gelatinaseassociated lipocalin (NGAL), is a secreted glycoprotein involved in iron trafficking. Increased LCN2 expression has been observed in ovarian (43), thyroid (44), breast (45,93), lung (94), colon (46), and pancreatic (95,96) cancers. In breast and thyroid cancers high LCN2 expression strongly correlated with advanced tumor grade and poor prognosis, but in ovarian, pancreatic and CRC it was associated well-differentiated tumors and a good prognosis (93).…”
Section: Iron Transportmentioning
confidence: 99%
“…LCN2 is abundantly expressed in various tissues such as immune cells, adipose tissue, lung, liver, kidney, and uterus, and is implicated in diseases associated with inflammation and obesity including inflammatory bowel disease, cardiovascular disease, acute kidney injury, acute pancreatitis, cancer, multiple sclerosis, and type 2 diabetes mellitus (T2DM) [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%